2021
DOI: 10.18388/abp.2020_5538
|View full text |Cite
|
Sign up to set email alerts
|

miR-379-5p inhibits proliferation and invasion of the endometrial cancer cells by inhibiting expression of ROR1

Abstract: Endometrial cancer is a common gynecological malignancy, and the incidence of this disease has increased in recent years. Recently, some studies suggested that the expression of miR-379-5p suppressed the metastasis of breast cancer cells. However, whether the expression of miR-379-5p could affect the proliferation, migration and invasion of endometrial cancer is unclear. In this study, we established miR-379-5p overexpression and miR-379-5p inhibition in endometrial cancer cells. Next, EdU and colony formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Furthermore, we noticed, the expressions of miR-379-5p and ROR1 mRNA were found to be negatively correlated. This finding was like that of Liang et al, (2021) who discovered that miR-379-5p targeted and restricted ROR1 expression, and that the effects of miR-379-5p overexpression on endometrial cancer cell proliferation, migration, and invasion were decreased after ROR1 overexpression. These findings revealed that miR379-5p inhibited endometrial cancer cell proliferation, migration, and invasion via decreasing ROR1.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Furthermore, we noticed, the expressions of miR-379-5p and ROR1 mRNA were found to be negatively correlated. This finding was like that of Liang et al, (2021) who discovered that miR-379-5p targeted and restricted ROR1 expression, and that the effects of miR-379-5p overexpression on endometrial cancer cell proliferation, migration, and invasion were decreased after ROR1 overexpression. These findings revealed that miR379-5p inhibited endometrial cancer cell proliferation, migration, and invasion via decreasing ROR1.…”
Section: Discussionsupporting
confidence: 79%
“…To our knowledge, this is the first study to investigate the expression patterns of miR-379-5p in endometrial cancer tissue, while Liang et al only looked at its expression in endometrial cell lines in their study (Liang et al, 2021). As a result, the focus of this research was on the expression of miR-379-5p in EC and the relationship between miR-379-5p and its potential target, ROR1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, miR-379-5p was overexpressed in most tumors. And overexpression of miR-379-5p in breast cancer cell lines and endometrial cancer cell lines significantly reduced the proliferative ability of cancer cell lines [ 38 , 39 ]. In this study, the expression of miR-379-5p was also found to be lower in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…LINC00665, for example, is known to accelerate breast cancer progression via the miR-379-5p/LIN28B pathway [ 30 ]. Alternately, miR-379-5p inhibits endometrial cancer cell proliferation and invasion via downregulation of RTK-like orphan receptor 1 (ROR1) levels [ 31 ]. Circ_SIPA1L1 induces osteosarcoma progression via the miR-379-5p/mitogen-activated protein kinase kinase kinase 9 (MAP3K9) pathway [ 32 ].…”
Section: Discussionmentioning
confidence: 99%